Leadership in Movement Disorders 2019
DOI: 10.1007/978-3-030-12967-5_20
|View full text |Cite
|
Sign up to set email alerts
|

JEON, Beomseok (BJ): Seoul/Republic of Korea

Abstract: This paper investigates the impact of observations on atmospheric state estimation in weather forecasting systems using graph neural networks (GNNs) and explainability methods. We integrate observation and Numerical Weather Prediction (NWP) points into a meteorological graph, extracting k-hop subgraphs centered on NWP points. Self-supervised GNNs are employed to estimate the atmospheric state by aggregating data within these k-hop radii. The study applies gradient-based explainability methods to quantify the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 92 publications
2
20
0
Order By: Relevance
“…This is consistent with the findings of Jeon, who discovered that younger, female participants had a greater tendency to use their time in an occupational balance. The study results also showed that younger adults were more active, and that females showed higher levels of ADL and IADL in comparison to males [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the findings of Jeon, who discovered that younger, female participants had a greater tendency to use their time in an occupational balance. The study results also showed that younger adults were more active, and that females showed higher levels of ADL and IADL in comparison to males [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, people who are not sufficiently provided with an opportunity to work can suffer from poor health and eventually they have difficulties with living. This demonstrates that OI may damage one’s health or cause diseases by worsening the qualitative aspects of one’s health and life [ 10 ]. Countries, therefore, need to be more aggressive in providing environments for older adults that improve their life satisfaction by maintaining the OB.…”
Section: Introductionmentioning
confidence: 99%
“…After the discontinuation of the Japanese health administration system, the Ministry of Health and Welfare established by the USAMGIK did not function very well due to a lack of human resources. Various infectious diseases epidemics broke out under the circumstances of the unclear roles of the police in containing infectious diseases outbreaks [7].…”
Section: Cholera Outbreaks and Epidemicsmentioning
confidence: 99%
“…The first report of terrestrial mammals in Dok-do was 40 domestic rabbits ( Oryctolagus cuniculus domesticus ), which were released for food supply by the police in 1973, and the rabbit population increased to 230 rabbits [ 13 ]. Fortunately, the rabbit removal project was started by Ulleung-Gun (county) in 1988, and the rabbits were completely removed by 1992 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%